Assessing the Indonesian Banking Risk: A Comparative Study between Islamic and Conventional Banks - Yona Friantina (Jurnal Internasional Penelitian Bisnis Terapan, 2019)
Technological advances and deregulation have driven banks to capitalize their benefits into some diversification activities they choose in the financial industry. This paper investigates the relation between service activities and risk of Indonesian banking industry in the period of 2015-2017. This study employs Structural Equation Modeling (SEM) with path analysis and multiple group analysis of 12 Islamic banks and 38 conventional banks. This study reveals that the Islamic banks appear to have more variable service activities and more stable risk than the conventional banks. For Islamic banks, non-financing income has a negative significant impact on bank risk; while commission income and trading income have a positive significant impact. Further, other non-financing income has a positive impact on bank risk. In the conventional banks, non-interest income has a positive impact on bank risk; while commission income has a negative impact. In addition, trading income also has a negative impact, and other non-interest income has a positive impact. These results imply that the Islamic banks emphasize the importance of expanding new service activities to reduce the risk. In conventional banks, diversified activities contribute to higher income volatility and debt level. Thus, they need to reduce the high cost of depositors which include savings, demand deposits, time deposits, and also interest costs of long-term debt as the sources of fund.